Antenna system for radiomonitoring stations - Щербина, Ольга Алімівна; Ільницький, Юрій Якович; Михальчук, Інна Іванівна (Science-based technologies, 2020)
The article deals with principles of building an antenna system with advanced features for radiomonitoring and radiocontrol stations. The developed antenna array with the primary signal processing device provides a number of important functions for radiomonitoring: automated space survey and identification of radiation source; automatic determination of the angular coordinates of radiation sources; suppression of interference at frequencies that are close to the frequency of the monitored radioemission; measurement of electric field intensity; measurement of radiation field polarization parameters. The synthesized block diagram of the antenna system is provided with a self-monitoring circuit, which guarantees timely failure detection and system support in working condition. The principles of controlling the position of radiation pattern for antenna arrays with a small number of elements are considered. With electrical control of the ray positions, the deformation of the radiation pattern occurs. This can lead to significant complications in signal extraction in the presence of interference at frequencies close to the signal frequency. During mechanical scanning, the shape of the radiation pattern remains unchanged, which provides greater accuracy when pointing at a radiation source than with electrical scanning. Given this, it is advisable to use mechanical control of the antenna position in space. The total pattern is used to review the space and identify radiation sources. If there is interference at a frequency close to the frequency of the controlled radiation source, it is necessary to proceed to monitor by the difference directivity pattern, which makes it possible to determine the angular position of the radiation sources. Main zero of diagram with a gradual rotational movement of antenna aperture is combined with the direction of radiation sources and thus determines to bear.